PENGARUH KOMPOS LIMBAH TEH HITAM (TEA FLUFF) TERHADAP PERTUMBUHAN BENIH TEH (Camellia sinensis (L.) Kuntze) - Restu Wulansari; Erdiansyah Rezamela (Jurnal Tanah dan Sumberdaya Lahan, 2020)
Tea nursery that commonly uses planting media that consist of 30% of subsoil and 70% of topsoil needs more additional planting media to improve growth. It has been reported that black tea factory waste (tea fluff) can be used as compost for planting medium of tea nursery. This research was conducted to apply tea fluff as an alternative planting medium for tea seedling at the tea nursery of Research Institute for Tea and Chincona. GMB7 clone was used as a tea plant. Ten treatments, i.e. 100% topsoil (negative control), subsoil and topsoil with a combination of 30:70% (positive control), 40:60% and 50:50%, and subsoil or topsoil mixed with tea fluff compost with a combination of 70:30%, 60:40% and 50:50%, were arranged in a randomized block design with three replications. The results showed that plant height and root dry weight increased with the application of 30-40% tea fluff compost on topsoil. The number of leaves increased in all treatments, the length of the roots increased with 30-50% tea fluff compost on the subsoil, and the percentage of live seeds decreased compared to positive controls. Therefore, tea fluff compost can be used as an alternative medium for tea seedlings by mixing it up to 40% on topsoil, and up to 50% on subsoil in a combination of 70% of topsoil and 30% of subsoil without mixing.